Sorption of Pb(ll) by poly(hydroxamic acid) grafted oil palm empty fruit bunch - Haron, M J (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
This paper describes the sorption of Pb(ll) from aqueous solution. Oil palm empty fruit bunch (OPEFB) fiber was first grafted with poly(methylacrylate) and then treated with hydroxylammonium chloride in alkaline medium to produce hydroxamic acid (PHA) grafted OPEFB. Sorption of Pb(ll) by PHA-OPEFB was maximum at pH 5. The sorption followed the Langmuir model with maximum capacityof 125.0 mg g-1 at 25 degrees C. The sorption process was exothermic, as shown by the negative value of enthalpy change, Delta H0. The free energy change (DeltaG0) for the sorption was negative, showing that the sorption process was spontaneous. A kinetic study showed that the Pb(ll) sorption followed a second order kinetic model